Colorado forest road field handbook - Edwards, Richard M., editor; Colorado State Forest Service, publisher (Colorado State University. Libraries, 2011)
This handbook discusses the major aspects of forest roads management as it relates to their design, location, inspection, maintenance and repair. Most private and state forest roads are already in existence, thus the primary focus of this publication is to assist landowners in the management of these in-place roads.
Editor: Richard M. Edwards
Keywords: cross-drainage structures; forest roads; wet-weather operations; inspection; maintenance; repair; road access; Colorado; stream crossings; road location